2022
DOI: 10.3390/jcm11051425
|View full text |Cite
|
Sign up to set email alerts
|

TMAO and Gut Microbial-Derived Metabolites TML and γBB Are Not Associated with Thrombotic Risk in Patients with Venous Thromboembolism

Abstract: Background: The present work evaluates the association between circulating concentrations of Trimethylamine-N-oxide (TMAO), gamma butyrobetaine (γBB), and trimetyllisine (TML) in controls and patients with venous thromboembolism (VTE) with coagulation parameters. Methods: The study involved 54 VTE patients and 57 controls. Platelet function, platelet hyperreactivity, platelet adhesiveness, thrombosis-associated parameters, and thrombin generation parameters were studied. Plasma TMAO, γBB, and TML determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…While we have not evaluated the gut microflora of our study group, there is evidence arising from the literature that cancer, especially gastrointestinal malignancies, is associated with alterations in colonic microbiota, leading to the higher production of TMA and its further oxidation into TMAO [ 51 ]. In one of the recent studies, males with higher TMAO levels in blood demonstrated lower gut microbial diversity and a higher abundance of Firmicutes in their mucosa of large intestines [ 52 , 53 ]. This finding was confirmed in another study conducted by Clara E et al where a higher colonic abundance of Firmicutes and Bacteroidetes in men was associated with an increase in blood TMAO levels after ingestion of its precursors, choline or carnitine, demonstrating the role of microbiota in determining how L-carnitine is further processed by microorganisms [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…While we have not evaluated the gut microflora of our study group, there is evidence arising from the literature that cancer, especially gastrointestinal malignancies, is associated with alterations in colonic microbiota, leading to the higher production of TMA and its further oxidation into TMAO [ 51 ]. In one of the recent studies, males with higher TMAO levels in blood demonstrated lower gut microbial diversity and a higher abundance of Firmicutes in their mucosa of large intestines [ 52 , 53 ]. This finding was confirmed in another study conducted by Clara E et al where a higher colonic abundance of Firmicutes and Bacteroidetes in men was associated with an increase in blood TMAO levels after ingestion of its precursors, choline or carnitine, demonstrating the role of microbiota in determining how L-carnitine is further processed by microorganisms [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first longitudinal study that evaluates the impact of glycemic control on circulating γBB and TMAO concentrations in newly diagnosed T2D subjects. Based on data from a previous publication of our group using the same methodology [ 28 ], T2D patients presented with increased metabolite levels compared to controls; therefore, a clinical intervention should be expected to have a similar impact on their levels. However, our results revealed that glycemic control optimization not only failed to reduce these gut-microbiota-derived metabolites, but increased them.…”
Section: Discussionmentioning
confidence: 99%